On the Optimal Rate of Obsolescence - Elettra Agliardi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1990)
In this paper the decision of adopting of new technologies is studied trought a multistage model. It incorporates multiple sequential technological innovations and the possibility of implementing that have already been discovered. It is shown how such decision is effected by the relevant parameters, that is, the cost of adoption, the probability of discovery, the discount factor Moreover, it is studied how the decision about adoption is effected by the presence of a rival.
Keywords: 330